ANALISIS PENGARUH PENDAPATAN, TINGKAT PENDIDIKAN, DAN TANGGUNGAN KELUARGA TERHADAP PENGAMBILAN PEMBIAYAAN ARRUM BPKB PADA PT. PEGADAIAN SYARIAH UNIT LANGSA BARO - Zikriatul Ulya (GoAcademica Research dan Publishing, 2021)
The purpose of this study was to determine the analysis of the effect of income, education level and family dependents on the taking of Arrum BPKB financing. By using quantitative research methods, where the population is 235 and the sample used as the subject in this study is 70 customers. The sampling method in this study used simple random sampling method, the data analysis model used multiple linear regression. Based on the results of the analysis and hypothesis testing partially income has a positive and significant effect on the taking of financing, the education level variable also has a positive and significant effect on the taking of financing, and the family dependent variable has a positive and significant effect on the taking of financing. The results of the simultaneous test show that the variables of income, education level and family dependents have a significant and significant influence on taking financing at the Langsa Baro Sharia Unit Pegadaian.